Brazilian livestock extensionists attitudes toward different fates for male dairy calves - De-Sousa, Karolini Tenffen; Benetton, Juliana Bernardes; Pinheiro Machado Filho, Luiz Carlos; Hötzel, Maria José (Frontiers in Veterinary Science, 2025)
Male calves are not economically attractive for most dairy farms in the current system and are therefore considered surplus in the dairy industry. The issue has gained growing attention in many countries, due to economic and animal welfare implications. It is known that livestock extensionists play a crucial role in facilitating change and promoting sustainable practices among the farming community. This study aimed to investigate the knowledge and attitudes of Brazilian dairy extensionist regarding three potential solutions to the issue of male dairy calves: the use of sexed semen, rearing for beef, and culling at birth. Livestock extensionists from different regions of Brazil (n = 344) participated in an online survey and answered closed (multiple choice and Likert scale) and open questions. Most participants (63%) were male, 61% with ages ranging from 19 to 35 years old and 49% held a graduate education in veterinary medicine. The practice of culling male calves was generally rejected as unethical, while the use of sexed semen to reduce the birth of males was seen as having positive ethical (75%), environmental (77%), and animal welfare (81%) implications. However, participants considered it difficult to implement in small farms due to its high cost. Raising male calves for beef production was perceived as more economically viable for small and medium size (49%) than for large dairy farms (32%). In general, participants considered the fate of male dairy calves a complex issue, suggesting the need for more than one alternative to address it effectively. However, extensionists acknowledged not discussing the topic with farmers, indicating a potential lack of awareness or interest in the issue. It is possible that participants may not have received sufficient training or engaged in discussions on animal welfare issues, as this is a relatively new subject during their professional development. The nascent nature of the issue in Brazil emphasizes the need for comprehensive education and knowledge exchange initiatives in the industry, to ensure that practitioners are well-prepared to adopt best practices in male calf management. This may foster local discourse on the topic and the development of contextualized knowledge, a crucial step for addressing aspects of dairy farming sustainability.